Prevalence and antibiotic resistance of Pasteurella multocida isolated from chicken in Ado-Ekiti metropolis - Victor, Atere; Mathew, Bamikole; Adekemi, Oluyege; Ayo, Ajurojo; Odunayo, Alo (International Journal of Scientific World, 2016)
Pasteurella multocida is a poultry bacterial pathogen causing fowl cholera in chicken. The prevalence and antibiotic susceptibility of P. multocida isolates from freshly dead chicken were determined. Ninety seven (97) freshly dead chicken from 23 different farms were analyzed for the presence of P. multocida. Swabs of the trachea and the liver of the necropsied chicken were activated on buffered peptone water and later cultured on blood agar and MacConkey agar. Pure culture of organisms were subjected to cultural and biochemical characterization. In vitro susceptibility of the pure isolates of P. multocida against 12 antimicrobial agents was determined using disk diffusion method. Twelve isolates of P. multocida were recovered from the chicken, with a prevalence of 12.4%. Nine of the isolates were recovered from the trachea and three from the liver. All the 12 isolates recovered from the birds were multi-resistant to the antibiotics used in this research. The antibiogram showed that all the isolates resisted ampicillin, amoxicillin/clavulinate, doxycycline and tylosine. Nitrofuratoin and gentamycin had the best antimicrobial activity with 25% and 50% resistance respectively. The resistance of other antibiotics are: Ofloxacin 75%, Ciprofloxacin 83.3%, Enrofloxacin 75%, Furasol 66.7%, Ceftazidime 91.7% and Cefuroxime 66.7%. This result showed that there is an emergence of multi- resistance in P. multocida, therefore it is important to carry out sensitivity test before administration of antibiotics in order to control fowl cholera.Â